(untitled) (Journal SCIENCEVOLUTION, 2024)
Water scarcity is a problem that requires urgent attention in the Tacna region of Peru. In this context, the objective of this study is to evaluate the performance of a filter bed using corn husk (chala) for the treatment of greywater in the automotive industry, based on the development of two filter bed designs. The first consisted of four treatments, each with four layers. In filters No. 03 and No. 04, two levels of corn husk were used to compare their performance with filters No. 01 and No. 02. The second design consisted of three treatments and three repetitions, each composed of a combination of sugarcane bagasse, sawdust and sand. The parameters to be evaluated were pH and turbidity. As a result, it was observed that the filter bed with corn husk in filter No. 1 presented the highest effectiveness, with an efficiency of 95.98%. In contrast, the sugarcane bagasse-based filter bed, in treatment 1, obtained an efficiency of 62.41%. In conclusion, it was found that corn husk is a promising option for the treatment of industrial wastewater, because the parameters are within an acceptable range.